2012
DOI: 10.1002/ffj.3118
|View full text |Cite
|
Sign up to set email alerts
|

Volatile constituents of the fruit of Garcinia atroviridis and their antibacterial and anti‐inflammatory activities

Abstract: The volatile constituents obtained by hydrodistillation of the fruit of Garcinia atroviridis were analysed by capillary GC and GC‐MS. Fifty‐six compounds representing 94.3% of the isolate were identified, among which sesquiterpenoids dominated. The most abundant components were (−)‐β‐caryophyllene (23.8%), β‐caryophyllene alcohol (15.6%) and α‐humulene (10.7%). The total volatiles and three of the constituents were assayed for antibacterial and anti‐inflammatory activities using the micro‐dilution assay and a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 108 publications
0
9
0
Order By: Relevance
“…Phytochemical studies on G. atroviridis have reported the presence of garcinia acid (hydroxycitric acid) and its lactone, atroviridin, atrovirisidone and atrovirinone as well as some organic acid and volatile constituents besides flavonoids or phenolic compounds . Hydroxycitric acid is the principal acid of fruit rinds of G. cambogia , G. indica and G. atroviridis .…”
Section: Resultsmentioning
confidence: 99%
“…Phytochemical studies on G. atroviridis have reported the presence of garcinia acid (hydroxycitric acid) and its lactone, atroviridin, atrovirisidone and atrovirinone as well as some organic acid and volatile constituents besides flavonoids or phenolic compounds . Hydroxycitric acid is the principal acid of fruit rinds of G. cambogia , G. indica and G. atroviridis .…”
Section: Resultsmentioning
confidence: 99%
“…The fruits, leaves, and stem bark extracts of G. atroviridis are found to be a rich source of bioactive secondary metabolites, including phenolic, flavonoid and tannin compounds such as xanthones (atroviridin), benzoquinones (atrovirinone), cambogin, garcinol, camboginal, triflavanone (garcineflavanone A) and biflavonols (garcineflavonol A) [ 20 , 21 , 22 ]. These phytochemicals have been reported to display diverse pharmacological activities including antioxidant [ 22 , 23 ], antimicrobial [ 23 , 24 ], anti-proliferative [ 17 , 23 , 25 ], anti-inflammatory [ 24 ], anti-cholinesterases [ 21 ] and anti-hyperlipidemic effects [ 20 ]. Interestingly, it has been reported that some of these phytometabolites such as phenolic compounds, were capable to transform inorganic silver ions into nanoparticles [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, (E)-β-farnesene (58.5%) and β-caryophyllene (16.9%) were dominated in the leaf EO. The stem bark EO composed mainly palmitoleic acid (51.9%), followed by palmitic acid (21.9%), and 3-methoxy-5-pentylphenol (5.5%) (8,9).…”
Section: Essential Oilsmentioning
confidence: 99%
“…The fruit EO of G. atroviridis was active towards Bacillus subtilis and Staphylococcus aureus with minimum inhibitory concentration (MIC) of 4.8 mg/mL. Meanwhile, it showed weak activity on Escherichia coli, Pseudomonas stutzeri and Salmonella typhimurium (8). Regarding the leaf EO of G. celebica, it showed better inhibition on B. subtilis and MRSA than Proteus mirabilis.…”
Section: Antimicrobial Activitymentioning
confidence: 99%